Bulk Nanostructured Materials with Multifunctional Properties - Sabirov, I.; Enikeev, N.A.; Murashkin, M.Yu.; Valiev, R.Z.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents a multifunctional approach to the design of bulk nanostructured metals through severe plastic deformation (SPD). Materials engineering has traditionally involved selecting a suitable material for a given application. However, modern engineering frequently requires materials with a set of multifunctional, often conflicting properties: Enhanced mechanical properties need to be combined with improved physical (electrical, magnetic, etc.) and/or chemical (corrosion resistance, biocompatibility) properties. So disparate materials properties need to be engineered and optimized simultaneously. These requirements have created a paradigm shift in which the classical materials selection approach is replaced by design of material microstructures to achieve certain performance requirements, subject to constraints on individual properties such as strength, conductivity, and corrosion resistance. Written by researchers at the forefront of this new materials design approach, the present volume provides a comprehensive introduction to multifunctional design of bulk nanostructured materials, with applications ranging from hydrogen storage to construction engineering.
From the Contents: Introduction -- Nanostructural design of materials for advanced properties -- Grain refinement via severe plastic deformation -- Multifunctional properties of bulk nanostructured metallic materials -- Superstrength and enhanced mechanical properties -- Improved physical and functional properties -- Applications Areas -- Ti-based materials in bio-medical engineering -- Nanostructured Al alloys and Cu in electrical engineering and micro-electro-mechanical systems.
Keywords: Nanotechnology; Nanochemistry; Nanoscale science; Nanoscience; Nanostructures; Metals; Nanotechnology; Nanotechnology and Microengineering; Nanochemistry; Nanoscale Science and Technology; Metallic Materials